Bahui praññʻ sūʹ toṅʻ sū layʻ sa mā koṅʻ cī ta ti ya ’a krimʻ ’a caññʻʺ ’a veʺ nhan̊ʻʹ 1971 khu nhacʻ, toṅʻ sū layʻ sa māʺ neʹ miṅʻʹ khvanʻʻʺ myāʺ. ([Raṅʻ Kunʻ] : Publisher not identified, 1971)
Speeches and discussion points on Peasants day celebration and the third time central people's farmers committee meeting.
Keywords: Burma -- History -- 20th century